Collapse scenarios of WTC 1 & 2 with extension to generic tall buildings - Usmani, Asif; Flint, Graeme; Jowsey, Allan; Roben, Charlotte; Torero, Jose L (My University, 2006)
This paper presents a summary of the author’s investigation into the collapse of tall buildings. A large number of computational analyses have been carried out at the University of Edinburgh (UoE) over the last 4 years in order to understand the collapse of the tall buildings of the World Trade Center (WTC) complex on September 11, 2001 following the terrorist attacks that day. The aim of these analyses has no been to carry out a “forensic” investigation (as this was done by official US government sponsored investigation by NIST, see wtc.nist.gov). The primary purpose of the UoE investigations was to understand the global collapse mechanisms of tall buildings as a result of extensive (involving multiple floors) fires and from these analyses identify any “generic” collapse mechanisms that may or may not exist. Such identification will allow the development of new design methods resulting in enhancing the safety and robustness of tall buildings again fire.
Keywords: collapse mechanism; fire safety; World Trade Centre